Type 2 Diabetes In Urban and Rural Areas: A Comparative Study - Emmi Bujawati; Rahmi Awaliah; Jumriani Ansar (Al-Sihah : The Public Health Science Journal, 2021)
Diabetes mellitus type 2 is one of the degenerative diseases whose mortality and morbidity rates continue to increase, both in urban and rural areas. Bulukumba Regency is one of the areas with the highest prevalence of type 2 diabetes mellitus. This study aimed to determine the differences in the determinants of the incidence of type 2 diabetes mellitus in urban and rural areas of the Bulukumba Regency in 2021. The type of research used is quantitative with an observational analytic approach and a cross-sectional study design. The population in this study were all people with type 2 diabetes mellitus in urban and rural areas of the Bulukumba Regency. The sample of this study amounted to 210 respondents consisting of 140 respondents in urban areas and 70 respondents in rural areas who were taken using purposive sampling technique with inclusion criteria, namely patients who do not have comorbidities or complications such as coronary heart disease, stroke, and kidney failure as well as patients who are not pregnant at the time of this study. Data were analyzed using the chi-square test. The results of this study indicate that there are differences in consumption of sugar-sweetened beverages (p = 0.032), consumption of fast food (p = 0.044), physical activity (p =0.001), and economic status (p=0.04) of people with type 2 diabetes mellitus in urban and rural areas. Meanwhile, there was no difference in smoking behavior (p=0.404) with type 2 diabetes mellitus in urban and rural areas of the Bulukumba Regency. Management of type 2 diabetes mellitus is important as early as possible so that the morbidity rate due to diabetes can be reduced in the future. The different risk factors between urban and rural areas should be taken into account.